Market acceptance of herbal-based skin care products in Kuching for Sarakraf Sdn. Bhd. / Vloreen Nity Mathew and Ardiana Mazwa Raudah - Mathew, Vloreen Nity; Amir Abdullah, Ardiana Mazwa Raudah (2010)
This research aims to determine the customer acceptance towards herbal-based skin care product by focusing on the customers’ perception, attitude and purchase intention towards herbal-based skin care product in general. Through this research, Sarakraf will be provided with market information which later will assist in making decisions on marketing their skin care product. In any new product development, it is crucial to find out what the market needs and wants to avoid failure of the product. This is due to the acceptance level of the market will determine how the product would perform in the market place. Therefore, the focus is on analyzing the motivating variables of consumer buying behaviour that will result in the sale which is the common indicator of market acceptance. This research was done using a survey technique by distributing questionnaire as the mean for collecting useful data for analysis. The main findings of the research proves level acceptance is positively influenced by the purchase intention. The two independent variables of perception and attitude are positively correlated towards purchase intention.